2012
DOI: 10.1093/cid/cis916
|View full text |Cite
|
Sign up to set email alerts
|

Cefepime Therapy for Monomicrobial Bacteremia Caused by Cefepime-Susceptible Extended-Spectrum Beta-Lactamase–Producing Enterobacteriaceae: MIC Matters

Abstract: Based on the current Clinical and Laboratory Standards Institute susceptible breakpoint of cefepime (minimum inhibitory concentration ≤ 8 μg/mL), cefepime definitive therapy is inferior to carbapenem therapy in treating patients with so-called cefepime-susceptible ESBL-producer bacteremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(108 citation statements)
references
References 29 publications
2
104
1
1
Order By: Relevance
“…Results of observational studies comparing the activity of cefepime and carbapenems for invasive ESBL infections have been conflicting with some studies showing no difference [39,40] and others suggesting cefepime therapy is inferior [38,41,42] (Table 4). Lee and colleagues conducted an observational study including 17 patients with ESBL bacteremia receiving cefepime therapy and 161 patients receiving carbapenem therapy [42].…”
Section: Cefepimementioning
confidence: 99%
See 1 more Smart Citation
“…Results of observational studies comparing the activity of cefepime and carbapenems for invasive ESBL infections have been conflicting with some studies showing no difference [39,40] and others suggesting cefepime therapy is inferior [38,41,42] (Table 4). Lee and colleagues conducted an observational study including 17 patients with ESBL bacteremia receiving cefepime therapy and 161 patients receiving carbapenem therapy [42].…”
Section: Cefepimementioning
confidence: 99%
“…Lee and colleagues conducted an observational study including 17 patients with ESBL bacteremia receiving cefepime therapy and 161 patients receiving carbapenem therapy [42]. Patients receiving carbapenems were over 7 times more likely to survive than patients receiving cefepime.…”
Section: Cefepimementioning
confidence: 99%
“…Such recommendations are controversial, and imply that an important proportion of ESBL producers, particularly isolates producing CTX-M enzymes, would be reported as susceptible to ceftazidime (and to a lesser extent to cefepime) [Rodriguez-Bañ o et al 2012c]. A recent retrospective cohort study found that cefepime (particularly when the MIC was 18 mg/liter) was independently associated with increased mortality among patients with bacteraemia due to ESBL-producing Enterobacteriaceae compared with carbapenems [Lee et al 2012]. In our opinion, there is still not enough information about the efficacy of active cephalosporins in the treatment of serious infections caused by ESBL producers, particularly for those from sources other than the urinary tract.…”
Section: Cephalosporinsmentioning
confidence: 99%
“…Additionally, it has been reported recently that KPC-2 expression in Enterobacteriaceae is not enough to confer cefepime resistance (17). On the other hand, cefepime therapy of infections due to ESBL-producing Enterobacteriaceae was recently associated with lower survival rates among patients infected with isolates showing cefepime MICs of Ͼ1 g/ml, within the CLSI susceptibility range (18). Therefore, more studies in animal models, pharmacokinetic/ pharmacodynamic modeling, and/or focused clinical trials appear necessary to provide conclusive evidence that cefepime is a useful treatment option for infections due to KPC-producing isolates that demonstrate in vitro susceptibility to this agent under current CLSI breakpoints.…”
mentioning
confidence: 99%